thnaks for your answer
asked May 17, 2015 in Pre-Algebra Answers by idhammuqoddas (120 points)
reshown May 24, 2015 by Rod

Your answer

Your name to display (optional):
Privacy: Your email address will only be used for sending these notifications.
Anti-spam verification:

To avoid this verification in future, please log in or register.

1 Answer

Do you mean: (1/x)+x=3, what does 1/x^2+x^2=?

Multiply first equation through by x: 1+x^2=3x. 1/x^2+x^2=(x^4+1)/x^2=(x^4+1)/(3x-1)=$\dfrac{x^4+1}{3x-1}$.

Solving the quadratic: x^2-3x+1=0 we get x=3/2+sqrt(5)/2=2.618 or 0.382 approx., making x^2=6.8541 or 0.1459. 1+x^2=3x=7.8541 or 1.1459.

(x^4+1)/(3x-1)=7, because x^2=3x-1=3(3/2+sqrt(5)/2)-1=7/2+3sqrt(5)/2. x^4=49/4+21sqrt(5)+45/4=47/2+21sqrt(5)/2. Therefore, x^4+1=49/2+21sqrt(5)/2 and 7(3x-1)=49/2+21sqrt(5)/2.

The solution is $\dfrac{x^4+1}{3x-1}$=7.

answered Jun 26, 2015 by Rod Top Rated User (486,860 points)

Related questions

Welcome to, where students, teachers and math enthusiasts can ask and answer any math question. Get help and answers to any math problem including algebra, trigonometry, geometry, calculus, trigonometry, fractions, solving expression, simplifying expressions and more. Get answers to math questions. Help is always 100% free!
79,816 questions
83,632 answers
66,552 users